2022
DOI: 10.2217/fon-2022-0063
|View full text |Cite
|
Sign up to set email alerts
|

IL-10 in cancer: an essential thermostatic regulator between homeostatic immunity and inflammation – a comprehensive review

Abstract: Cytokines are soluble proteins that mediate intercellular signaling regulating immune and inflammatory responses. Cytokine modulation represents a promising cancer immunotherapy approach for immune-mediated tumor regression. However, redundancy in cytokine signaling and cytokines' pleiotropy, narrow therapeutic window, systemic toxicity, short half-life and limited efficacy represent outstanding challenges for cytokine-based cancer immunotherapies. Recently, there has been interest in the paradoxical role of I… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
4
1

Citation Types

2
8
0

Year Published

2022
2022
2024
2024

Publication Types

Select...
7

Relationship

0
7

Authors

Journals

citations
Cited by 15 publications
(10 citation statements)
references
References 108 publications
2
8
0
Order By: Relevance
“…In line with previous findings, 28 we observed that IL-10 was upregulated in metastatic sites compared to healthy liver in mouse. The role of IL-10 in various cancer types seems to be controversial.…”
Section: Discussionsupporting
confidence: 93%
See 2 more Smart Citations
“…In line with previous findings, 28 we observed that IL-10 was upregulated in metastatic sites compared to healthy liver in mouse. The role of IL-10 in various cancer types seems to be controversial.…”
Section: Discussionsupporting
confidence: 93%
“…By using cell-specific IL-10Ra-deficient mouse models, we found that IL-10Ra depletion in myeloid cells and Foxp3+Tregs resulted in significantly less liver metastasis. Consistent with previous studies analyzing the role of IL-10Ra on Foxp3+Tregs during colitis, 28 we showed that IL-10 signaling in Foxp3+Tregs was important to boost IL-10 production. Furthermore, impaired IL-10 signaling in Foxp3+Tregs did not affect the frequency of Foxp3+Tregs.…”
Section: Discussionsupporting
confidence: 92%
See 1 more Smart Citation
“…IL-10 levels remained stable after ablation in both groups of patients; however, Leuchte et al ( 22 ) demonstrated that IL-10 is notably modulated after ablation. The role of IL-10 in tumors is bidirectional, demonstrating protumor effects as a Th2-type cytokine ( 65 ). Qiao et al ( 66 ) reported that IL-10 notably exhibits antitumor effects by preventing dendritic cell-mediated apoptosis of CD8+ T cells; however, further clarification of the antitumor role of IL-10 is required.…”
Section: Discussionmentioning
confidence: 99%
“…It has been suggested that chronic low-level inflammation is one of the most important causes of insulin resistance onset, since chronic exposure to pro-inflammatory cytokines can impair insulin signaling pathways and decrease insulin secretion from beta cells [ 5 ]. Inflammation is the result of cellular damage and characterizes many pathologies, including cancer [ 11 , 12 , 13 ] and immune diseases [ 14 ], but also pregnancy complications, such as preeclampsia and preterm birth [ 15 , 16 , 17 , 18 ]. Chronic low-grade inflammation is a pathological condition, playing an important role in the pathogenesis and progression of some pathologies, including GDM, metabolic syndrome, DM and cardiovascular diseases [ 19 , 20 ].…”
Section: Introductionmentioning
confidence: 99%